IMPLEMENTASI GOOD GOVERNANCE MENUJU TERWUJUDNYA NEGARA BEBAS KKN DI INDONESIA - Agus, Andi Aco (Makassar Journal of Social Sciences, 2015)
Abstract: The existence of good governance or good governance are often called for in fact hail hail is still a dream and was limited to mere jargon. Indonesia should immediately awakened from a long hibernation. Revolution in every field should be done because every product produced only accommodate the interests of political parties, factions and groups of people. When it should be good governance should be a serious concern. Transparency can indeed be one solution, but whether it's enough just to achieve good governance. Good concept governances, the process of implementation of state power in implementing the provision of public goods and service called governance (government or governance), while the so-called best practices of good governance (good governance). In order for "good governance" can become a reality and create state fair, it takes the commitment and involvement of all stakeholders, namely the government and society. Good governance demands effective "alignement" (coordination) is good and the integrity, professional and work ethic and high moral. Thus the application of the concept of "good governance" in the administration of state government power is a challenge. The implementation of good governance is a major prerequisite for realizing the aspirations of the community in achieving the goals and ideals of the nation. In order that requires the development and implementation of appropriate systems of accountability, clear, and real so that the implementation of the government and development can take place in efficient, effective, clean and accountable and corruption-free